International Financial Statistics, October 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This October 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS publish, for most countries of the world, current data on exchange rates, international liquidity, international banking, money and banking, interest rates, prices, production, international transactions (including balance of payments and international investment position), government finance, and national accounts. The notes to the country tables in the monthly issues provide information about exceptions in the choice of the consumer price index and the period average exchange rate index. Since January 1, 1981, the value of the SDR has been determined based on the currencies of the five member countries having the largest exports of goods and services during the five-year period ending one year before the date of the latest revision to the valuation basket.